Evaluation of Cortical Bone Thickness of Posterior Implant Sites Using CBCT in Iraqi Population - Nuhad A Hassan; Aseel S. Khazaal Al-Jaboori; Afya Sahib Diab Al-Radha (Hindawi Limited, 2022)
Background. Cortical bone thickness (CBT) is a critical factor for implant success and for determining the long-term dental implant treatment outcome. Objectives. The objective of this investigation was to examine posterior cortical bone thickness buccally and lingually in dentate and edentulous implant sites according to gender. Materials and Methods. CBT of 160 patients requiring a single posterior tooth implant was investigated by CBCT. The study included 80 males and 80 females. CBT was measured for implant edentulous sites at 3 levels including crestal bone (level 1), five mm from the crest (level 2), and ten mm from the crest (level 3). CBT was also measured for dentate sites at 3 levels including crestal bone (level 1), midroot bone (level 2), and apical portion (level 3). The differences of bone thickness between the levels of dentate sites were statistically analyzed using a Kruskal-Wallis one-way analysis of variance. Mann-Whitney test was used to determine the specific differences between group members. For the edentulous site, a one-way ANOVA was used. Results. CBT increased gradually from the crestal level to the apical level in all groups (buccal and lingual side, male and female). However, CBT at lingual side was statistically higher than that at buccal side in all groups. The mean value of CBT was significantly higher in males than females for both edentulous and dentate site. The dentate site shows a higher CBT in the apical level than the edentulous group in both male and female/buccal and lingual groups. Conclusion. CBT at the coronal levels is low and susceptible for resorption compared to the apical portion, especially for the female group. Moreover, CBT is thicker in males than females. It is essential to measure the CBT before making a treatment plan with dental implant prosthesis.